1977
DOI: 10.1073/pnas.74.9.4046
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysin biosynthesis in normal rats and in rats with hereditary diabetes insipidus.

Abstract: When [35S]cysteine was injected adjacent to the supraoptic nucleus (SON) in rats, it was rapidly incorporated into proteins in the SON. The [35S]cysteine-labeled proteins extracted from the SON were separated by isoelectric focusing on polyacrylamide gels. Twenty minutes after the injection of [I Scysteine, two major labeled peaks (pI = 5.4 and 6.1) were found in the SON of normal rats; Brattleboro rats had only one major labeled peak (pI = 5.4). One hour after the injection, four major radioactive peaks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1978
1978
1995
1995

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…The above-reported observations reinforce and extend the previous findings from pulse-chase analysis by others [7,8,15] that neurophysin biosynthesis may occur via higher molecular weight precursors. In addition to the '17 k' form, we are able also to detect a =;> '20 k' species which seems to be relatively labile and could preferably be isolated as a product of in vitro translation of reticulum-bound polysomes from hypothalamic neurons.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The above-reported observations reinforce and extend the previous findings from pulse-chase analysis by others [7,8,15] that neurophysin biosynthesis may occur via higher molecular weight precursors. In addition to the '17 k' form, we are able also to detect a =;> '20 k' species which seems to be relatively labile and could preferably be isolated as a product of in vitro translation of reticulum-bound polysomes from hypothalamic neurons.…”
Section: Discussionsupporting
confidence: 90%
“…These larger forms, elaborated on the rough-surfaced endoplasmic reticulum [5,6], undergo several transformations, named processing, which generally lead to the unmasking of biologically active 'final' compounds. Biosynthetic evidence [7,8] for such a general scheme, derived from in vivo pulse chase experiments, seems to apply to the biogenesis of the neurophysins, neurohypophyseal hormone-associated proteins, synthesized by neurosecretory neurons of the magnocellular system in the supraopticus and paraventricular nuclei of the hypothalamus. In the course of our biochemical approach to the characterization of such putative pro-neurophysins we were able to detect, using a radioimmunological assay, neurophysin-like materials with molecular weight '17 k' and ~ '20 k'.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, bovine hypothalamic messenger (m)RNA has been shown to direct the synthesis of possible neurophysin biosynthetic precursors in a cell-free system (16)(17)(18). Similarly, it has been reported that labeled cysteine injected adjacent to the supraoptic nucleus of the rat was rapidly incorporated into a 20,000-dalton protein that, in time, was converted to a 12,000-dalton protein (19,20). Along with the findings that the 20,000-dalton protein reacts with antineurophysin serum (21) and that trypsin liberates neurophysin and vasopressin-like peptide from the protein (22), these authors suggested that this 20,000-dalton protein may be a precursor to neurophysin and vasopressin in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…Relaxin also causes a pressor and tachycardic response in Brattleboro rats (41); animals which do not sjnthesize and secrete a functional vasopressin molecule (43). The mechanism of this pressor response is not established but Parry showed that exogenous relaxin causes a substantial release of oxytocin in Brattleboro rats (41 ) and this oxytocin may be responsible for the cardiovascular actions.…”
Section: Effects Of Relaxin On Vasopressin Secretion and Hemodynamic mentioning
confidence: 99%